PROMOTING INNOVATION VIA INDUSTRY-ACADEMIA COOPERATION: AN EXAMINATION OF UNDERGRADUATE STUDENTS IN INDIA - Neihsial, H Lamminlun; Bhardwaj, Broto (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In a rapidly evolving global economy, industry-academia collaboration has emerged as a key driver of innovation and skill development. These partnerships offer unique opportunities to bridge the knowledge gap between theory and practice in India, a nation with an increasing number of undergraduate students. This study examines the ways in which industry-academia collaboration can enhance the educational and career prospects of Indian undergraduate students. The paper uses theoretical frameworks, case studies, and empirical data to highlight the key benefits, challenges, and strategies for promoting such collaborations. Particular emphasis is placed on their capacity to boost employability, promote entrepreneurship, and develop a workforce equipped to handle the problems of the twenty-first century. The findings emphasise that in order to optimise the impact on students and the larger innovation ecosystem, long-term, planned partnerships supported by legislative acts are required.